Aspergillosis of the central nervous system: A catastrophic opportunistic infection - Piya Pongbhaesaj (2018)
The clinical features and outcome of the treatment of aspergillosis of the central nervous system (CNS) in Thai patients are presented. The patients who were diagnosed as having CNS aspergillosis by tissue biopsy or culture from January 1,1991 to December 31, 2000 were retrospectively reviewed. The study variables including age, sex, underlying disease, symptoms and signs, neuro-imaging studies, pathological findings and outcome of treatment, are described. There were seven cases of aspergillosis of the central nervous system. Four patients were male. The median age was 65 years (range 36-78 years). The most common underlying disease was diabetes mellitus (4/7; 57.1%). Two patients (28.6%) had no underlying disease. The most common primary site of infection was the paranasal sinuses (6/7; 85.7%). The most common clinical presentation was headache (6/7; 85.7%). Common neurological signs included multiple cranial nerve palsies (5/7; 71.4%) and alteration of consciousness (3/7; 42.9%). The median duration of the symptoms prior to admission was 60 days (range 8-180 days). All patients were treated with intravenous antifungal agents at high doses. Extensive surgery was performed in 6 patients. The mortality rate was very high (6/7; 85.7%). The median time from diagnosis and treatment to death was 53 days (22-720 days). Aspergillosis of the CNS should be considered in those with clinical features of headache, multiple cranial nerve palsies and alteration of consciousness accompanied by sinusitis, especially in elderly and diabetic patients. It remains a catastrophic opportunistic infection in spite of the current intensive and aggressive treatment.